2019
DOI: 10.5114/ada.2018.77726
|View full text |Cite
|
Sign up to set email alerts
|

Clinic experience in discoid lupus erythematosus: a retrospective study of 132 cases

Abstract: Introduction: Lupus erythematosus (LE) is an autoimmune disease characterized by a broad range of cutaneous manifestations. Discoid LE (DLE) is the most common chronic manifestation of LE. Literature reviews show that there are a limited number of large-series studies investigating DLE. Additionally, there is still no consensus on the etiological factors of DLE such as sun exposure and smoking. Aim: To evaluate the clinical and demographic characteristics of patients with DLE. Material and methods: The study i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
(26 reference statements)
0
4
0
1
Order By: Relevance
“…UVB wavelength can significantly induce skin inflammation in patients with SLE 7–9 . Chronic UV exposure is also an important risk factor for DLE 10 . However, the mechanisms through which SLE and DLE skin is predisposed to persistent inflammation following UVB exposure are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…UVB wavelength can significantly induce skin inflammation in patients with SLE 7–9 . Chronic UV exposure is also an important risk factor for DLE 10 . However, the mechanisms through which SLE and DLE skin is predisposed to persistent inflammation following UVB exposure are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Another study found ANA positivity in only 23.7% of patients. 26 This study examined various predictors that resulted in adverse pregnancy outcomes. A significant association was found between HTN and miscarriage, preterm birth, pre-eclampsia and LN.…”
Section: Discussionmentioning
confidence: 99%
“…There were previous reports investigating rates of positive family history for discoid lupus erythematosus (DLE) in DLE patient cohorts. However, the rate varied significantly among different studies, ranging from 0% to 20% 2–5. The differences in rates were likely due to the populations studied and differences in whether family histories included first-degree relatives and/or more distant relatives.…”
Section: Introductionmentioning
confidence: 93%
“…However, the rate varied significantly among different studies, ranging from 0% to 20%. [2][3][4][5] The differences in rates were likely due to the populations studied and differences in whether family histories included first-degree relatives and/or more distant relatives. Other limitations were small sample size, homogeneous racial or ethnic populations, and lack of inclusion of other subtypes of CLE.…”
Section: Introductionmentioning
confidence: 99%